56.4k views
3 votes
If r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to mc015-1.jpg?

If r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to mc015-1.jpg-example-1

2 Answers

5 votes
3(6)-1/2(6)+1 is the correct answer

User Jstephenson
by
6.1k points
5 votes

we have


r(x) = 3x - 1\\s(x) = 2x + 1

we know that

the ratio
(r)/(s)(x) is equal to


(3x-1)/(2x+1)

for
x=6

substitute the value of x in the equation


(3(6)-1)/(2(6)+1)

therefore

the answer is the first option


(3(6)-1)/(2(6)+1)

User Jose Santos
by
5.9k points